Carotid artery infusion via implantable catheters for squamous cell carcinoma of the tonsils - Karl Reinhard Aigner (World Journal of Surgical Oncology, 2018)
Abstract Background Chemoradiotherapy has a dominant role in therapy for head and neck cancers. However, impressive results are often disturbed by adverse events such as dysphagia, xerostomia, and functional speech and hearing loss. To avoid exceeding toxicity limits in patients with primary and recurrent cancers of the tonsils, chemotherapy was administered intra-arterially via implantable Jet-Port-Allround catheters. Methods We report on patients with primary and recurrent cancers of the tonsils. Eleven patients who refused chemoradiation were included in this trial. Of the seven patients without prior therapy, one was stage I, one was stage III, three were stage IVA, one was stage IVB, and one was stage IVC. The four patients who were in progression after prior chemoradiation were stage IVA. The median follow-up time was 47 months (20 to 125 months). After the implantation of a Jet-Port-Allround catheter into the carotid artery, the patients received intra-arterial infusion chemotherapy with venous chemofiltration for systemic detoxification. The stage I patient received lower-dose chemotherapy without chemofiltration. The stage IVC patient with lung metastases and a primary tumor that extended across the midline to the contralateral tonsil received additional isolated thoracic perfusion chemotherapy. Results All seven chemoradiation-naïve patients exhibited clinically complete responses and are still alive after 20 to 125 months. Among the four patients who had relapsed after prior chemoradiation, the intra-arterial therapy elicited only poor responses, and the median survival time was 7.5 months. After carotid artery infusion chemotherapy, none of the patients required tube feeding. No cases of dysphagia, xerostomia, or functional speech and hearing loss have been reported among the patients without prior chemoradiotherapy. Conclusion Despite the administration of low total dosages, intra-arterial infusion generates high concentrations of chemotherapeutics. In combination with chemofiltration, the systemic toxicity is kept within acceptable limits. Among the non-pretreated patients, better tumor responses and long-term tumor control were noted compared with those who had prior chemoradiation. Implantable Jet-Port-Allround carotid artery catheters facilitate the application of regional chemotherapy.